2006
DOI: 10.2136/sssaj2005.0104
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of Fertilizer Application Rate on Nitrous Oxide Emissions

Abstract: The attribution of N2O emission factors to N inputs from chemical fertilizers requires an understanding of how those inputs affect the biological processes from which these emissions are generated. We propose a detailed model of soil N transformations as part of the ecosystem model ecosys for use in attributing N2O emission factors to fertilizer use. In this model, the key biological processes—mineralization, immobilization, nitrification, denitrification, root, and mycorrhizal uptake—controlling the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 48 publications
2
84
1
3
Order By: Relevance
“…1). Non-linear relationships have also been found in corn and wheat systems in Ontario and Alberta, (Grant et al 2006;Ma et al 2009). Emissions of N 2 O may therefore exhibit a threshold response related to crop N requirement and the magnitude of N input (Erickson et al 2001).…”
Section: Summary Of Evidencementioning
confidence: 95%
See 1 more Smart Citation
“…1). Non-linear relationships have also been found in corn and wheat systems in Ontario and Alberta, (Grant et al 2006;Ma et al 2009). Emissions of N 2 O may therefore exhibit a threshold response related to crop N requirement and the magnitude of N input (Erickson et al 2001).…”
Section: Summary Of Evidencementioning
confidence: 95%
“…Evidence from high resolution N fertilizer gradients in Michigan (McSwiney and Robertson 2005;Hoben et al 2010, in review;Millar et al 2010, in review) suggest that N 2 O emissions increase exponentially with increasing fertilizer N rate, particularly at high rates that exceed the ecosystem (crop+soil) N uptake capacity (Grant et al 2006). In a 3 year continuous corn experiment with nine fertilizer N rates from 0 to 291 kg N ha −1 yr −1 , McSwiney and Robertson (2005) discovered a non-linear relationship between N rate and emissions of N 2 O, with fluxes remaining low and relatively stable at low N rates, and rapidly increasing at N rates beyond which crop yield was maximized.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Flechard et al [2007] observed N 2 O emission factors, which were consequently smaller for dry years than for other years. For boreal sub humid climates, Grant et al [2006] already advised to decrease emission factors for dry years.…”
Section: Analysis Of Temporal Resolution Effectmentioning
confidence: 99%
“…The response curves of N 2 O emissions as a function of the fertilizer rate are not common. Only a few studies that have utilized fertilized treatments with more than two nitrogen levels could obtain functional relationships between N 2 O emissions and fertilizer rates (Grant et al, 2006;Mosier et al, 2006;Halvorson et al, 2008;Hoben et al, 2011). When fertilizer rates are in excess of the amount required to optimize crop growth, N 2 O emissions are stimulated (McSwiney and Robertson, 2005;Zebarth et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…When fertilizer rates are in excess of the amount required to optimize crop growth, N 2 O emissions are stimulated (McSwiney and Robertson, 2005;Zebarth et al, 2008). Some studies reported the N 2 O emissions exponentially increased with fertilizer rates (Grant et al, 2006;Hoben et al, 2011), but because of the complexity of agricultural management and natural conditions, the functional relationships may not be nonlinear. Hoben et al (2011) obtained both linear and nonlinear relationships for different years and sites with on-farm maize crops in the US Midwest.…”
Section: Introductionmentioning
confidence: 99%